Analisa Proksimat dan Kadar Kafein Pada Green Bean Robusta Berdasarkan Lama Waktu Fermentasi - Rosdiana, Eva; Nirmala Kusumaningtyas, Rizky; Galuh Pratita, Dian; Lutfi Alwi , Annisa; Rahayu , Sri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2022)
Coffee is one of the commodities that provide additional foreign exchange for Indonesia. This is supported by the position of the country of Indonesia which is the number 4 producer of coffee beans in the world. One type of coffee that is cultivated in Indonesia is Robusta coffee. Robusta coffee is known as coffee that is resistant to various diseases and extreme environments, has superior properties and is very fast growing, therefore Robusta coffee is widely chosen to be planted by Indonesian. One of the step at coffee processing by full wash processing is fermentation. Fermentation is a process that produces chemical reactions involving other microorganism that breaking down polysaccharide into enzyme and monosaccharide. That process itself is influenced by several factors, including the number of bacterial inoculum, fermentation time, substrate (medium), temperature, oxygen, water and acidity (pH). The incubation period of fermentation is the most step that determine the quality of coffee. The purpose of this study was to determine the effect of the length of fermentation time on the wet coffee processing method on green beans robusta that produced by looking at several chemical parameters, including water content, ash content, fat content, carbohydrate content and caffeine content. The results showed that variations in fermentation time had a significant effect on the parameters of water content, ash, carbohydrates, fat and caffeine.